ANTARA SUNNAH DAN TRADISI : Analisis Hadits Tentang Doa Pernikahan Riwayat Abu Daud No. 1819 - Nur'aeni, Ulvah; H.U. Saifuddin ASM (AL ISNAD: Journal of Indonesian Hadith Studies, 2025)
This study aims to analyze the hadith about the prayer offered by the Prophet for the bride and groom during the wedding. This hadith is raised to criticize the tradition of prayers for brides such as to achieve Sakinah mawaddah wa Rahmah, immediately get offspring, and other prayer traditions that spread in the community. An in-depth study of the hadith from Abu Daud's narration number 1819 will answer at least two main questions in this research. What is the correct wording of the prayer based on the Sunnah of the Prophet? What is the meaning of the prayer, what is its essence, and what is the philosophy of the prayer? These two formulations will be answered with seven steps of hadith research consisting of tautsiq, takhrij, tashhih, tanasub, tarikh, tahlil, and tathbiq. Based on this methodology, the study concludes that this hadith emphasizes that what should be prayed for newlyweds is attaining blessings and goodness in their marriage through mutual cooperation, rather than just compatibility and offspring. The couple should strive together to continuously increase in goodness in all aspects of life. Marriage unites two different individuals, so the spouses should unite their love, aspirations, and efforts to achieve happiness and overcome challenges together.